Credit risk and collateral demand in a retail payment system - Hector Perez-Saiz; Gabriel Xerri (Bank of Canada, 2016)
The recent financial crisis has led to the development of new regulations to control risk in designated payment systems, and the implementation of new credit risk management standards is one of the key issues. In this paper, we study various credit risk management schemes for the Canadian retail payment system (ACSS) that are designed to cover the exposure of a defaulting member. We consider schemes that use a collateral pool calculated using a rolling time window. Our simulations show that the size of the window has a very significant effect on the average level of collateral and its variability day to day, creating an interesting trade-off. Collateral levels and variability may be important for ACSS participants because they could affect the opportunity costs of pledging collateral, and also the costs of managing it over time. Our results contribute to understanding the practical implementation of risk management schemes in the current and future generations of payment systems in Canada.
Keywords: G21; G23; C58; 330; Econometric and statistical methods; Financial stability; Payment clearing and settlement systems